SAT0072 Frequency of interferon-gamma-positive TH17 (TH17-1) cells is up-regulated in synovial fluids in patients with rheumatoid arthritis. (23rd January 2014) - Sakurai, N.; Hidekazu, I.; Kayakabe, K.; Sakairi, T.; Kaneko, Y.; Maeshima, A.; Hiromura, K.; Nojima, Y.
Abstract : Background: Th17 cells are a recently identified CD4 + CD45RO + helper T cell subset that produce IL-17 with proinflammatory actions and are thought to play a critical role in the pathogenesis of collagen-induced arthritis (CIA), a murine model of rheumatoid arthritis (RA) (1). Recently, Nistala et al. showed that Th17 cells obtained from the synovial fluid (SF) of juvenile idiopathic arthritis (JIA) patients co-expressed IFN-γ (2). Moreover, they found that Th17-1 cells (Th17 cells co-expressing IFN-γ) were enriched in SF compared to peripheral blood mononuclear cells (PBMC) in patients with JIA. However Th17-1 has not been investigated in patients with RA. Objectives: To explore the significance of Th17-1 in human RA, we examined the frequency of Th1, Th17, and Th17-1 cells in PBMC and SF derived from RA patients by flow cytometry and compared them with those in PBMC from healthy donors. Methods: PBMC from 14 healthy donors (Control-PBMC) and 33 RA patients (RA-PBMC), and SF from 17 RA patients (RA-SF) were obtained and used in this experiment. Isolated mononuclear cells were stimulated with PMA and ionomycin for 5 hours, and then the expression of intracellular cytokines and cell surface markers were analyzed by flow cytometry. Among double positive cells for CD4 and CD45RO, single positive cells for IFN-γ or IL-17, and double positive cells for both IFN-γ and IL-17 were defined as Th1, Th17, and Th17-1 cells, respectively. Results: The frequency of Th17 and Th17-1 cells in PBMC from RA patients were significantly lower than those from controls, whereas the frequency of Th1 cells were similar between them (Th17, 2.2±1.1% vs. 3.0±1.1%, P=0.006; Th17-1, 0.4±0.3% vs. 1.0±0.5%, P=0.0002; Th1, 24±11% vs. 28±5.6%, P=0.0624; RA-PBMC vs. Control-PBMC). Among RA patients, the frequency of Th17 cells in SF was significantly lower than that of PBMC, whereas Th1 and Th17-1 cells in SF were significantly higher than those in PBMC (Th17, 2.2±1.1% vs. 1.8±1.4%, P=0.0381; Th1, 24±11% vs. 38±14%, P=0.0004; Th17-1, 0.4±0.3% vs. 1.1±0.9%, P=0.0006; RA-PBMC vs. RA-SF). Conclusions: In patients with RA, the frequency of both Th1 and Th17-1 cells but not of Th17 in SF were significantly up-regulated, suggesting that a local inflammation in RA joints is dominantly mediated by IFN-γ. References: Korn T, Bettelli E, Oukka M, Kuchroo VK. IL-17 and Th17 Cells. Annu Rev Immunol. 2009. 27:485–517. Nistala K, Adams S, Cambrook H, Ursu S, Olivito B, de Jager W, Evans JG, Cimaz R, Bajaj-Elliott M, Wedderburn LR. Th17 plasticity in human autoimmune arthritis is driven by the inflammatory environment. Proc Natl Acad Sci U S A. 2010. Aug 17;107(33):14751-6. Disclosure of Interest: None Declared